1995
DOI: 10.1038/bjc.1995.519
|View full text |Cite
|
Sign up to set email alerts
|

Differences in resistance to 5-fluorouracil as a function of cell cycle delay and not apoptosis

Abstract: Summary A series of human embryo fibroblasts has previously been shown to display increasing resistance to the antimetabolites methotrexate (MTX) and N-phosphonacetyl-L-aspartate (PALA) with increasing tumorigenicity. This increased resistance was found to be further increased as a result of salvage pathway activity for purine and pyrimidine biosynthesis. A similar pattern of increasing resistance paralleling increasing tumorigenicity has now been shown to occur with 5-fluorouracil (5-FU), which is independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Three mechanisms of the cytotoxic action of 5‐FU have been proposed: 1) 5‐FU is metabolized to 5‐fluorodeoxyuridine monophosphate(FdUMP), which suppresses thymidylate synthetase (TS) and subsequently inhibits DNA synthesis18; 2) the incorporation of FdUMP into nuclear RNA has important metabolic consequences for the cell that lead to cytotoxity19, 20; and 3) 5‐FU residues are incorporated directly into DNA, resulting in DNA damage as a consequence of ineffective repair 21, 22. Of the three mechanisms, the third may account for 5‐FU‐induced apoptosis,23, 24 whereas the first likely predominates in cell cycle effects, including partial synchronization of cycling cells in the S‐phase and subsequent retarded progression through the rest of the cell cycle 25–29…”
Section: Discussionmentioning
confidence: 99%
“…Three mechanisms of the cytotoxic action of 5‐FU have been proposed: 1) 5‐FU is metabolized to 5‐fluorodeoxyuridine monophosphate(FdUMP), which suppresses thymidylate synthetase (TS) and subsequently inhibits DNA synthesis18; 2) the incorporation of FdUMP into nuclear RNA has important metabolic consequences for the cell that lead to cytotoxity19, 20; and 3) 5‐FU residues are incorporated directly into DNA, resulting in DNA damage as a consequence of ineffective repair 21, 22. Of the three mechanisms, the third may account for 5‐FU‐induced apoptosis,23, 24 whereas the first likely predominates in cell cycle effects, including partial synchronization of cycling cells in the S‐phase and subsequent retarded progression through the rest of the cell cycle 25–29…”
Section: Discussionmentioning
confidence: 99%
“…Nabeya et al and Pickard et al reported that 5‐FU induced expression of the wild‐type p53 gene, followed by the induction of transcription of a variety of genes, including transcriptional factors such as Bax and p21; this resulted in arrest of cell growth and induction of apoptosis 2, 3. We demonstrated that 5‐FU induced apoptosis in human gastric carcinoma cell lines MKN‐45 and MKN‐74, which carry the wild‐type p53 gene, but not in MKN‐28 (which carries a mutated p53 gene) or in KATO‐III (which lacks the gene) 4.…”
mentioning
confidence: 99%
“…5-FdUMP in turn can inhibit thymidylate synthase, restricting de novo synthesis of thymidine monophosphate, and can ultimately inhibit the synthesis of DNA 26 . It has also been reported that 5-FU can induce apoptosis in some cancer cells 27,28 which in turn might stimulate the immune system. It is possible that treatment with 5′-DFUR might be selective for the inhibition of angiogenesis in ovarian tumors with high thymidine phosphorylase expression or high PSV.…”
Section: Discussionmentioning
confidence: 97%